2016
DOI: 10.1051/shsconf/20162801076
|View full text |Cite
|
Sign up to set email alerts
|

Universities’ visual image and Internet communication

Abstract: Abstract. Universities of the 21st century are built on digital walls and on the Internet foundation. Their "real virtuality" of Ɇ. Castells is represented by information and communication flows that reflect various areas: education, research, culture, leisure, and others. The visual image of a university is the bridge that connects its physical and digital reality and identifies it within the information flow on the Internet. Visual image identification on the Internet and the function that the visual image p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It is very important for young people to be at the center of all events, to acquire their own life experience, to be aware of all current trends, to be an active member of society. First of all, communication for them is a direct source of information (Kuimova, Kiyanitsyna & Truntyagin, 2016;Sazanov, 2010 Polytechnic University has created a website that can be a powerful tool for building ICT competencies for teachers and students (Okushova, Stakhovskaya & Sharaev, 2016). However, the survey has found that only 6% of respondents regularly visit the site.…”
Section: Research Questionsmentioning
confidence: 99%
“…It is very important for young people to be at the center of all events, to acquire their own life experience, to be aware of all current trends, to be an active member of society. First of all, communication for them is a direct source of information (Kuimova, Kiyanitsyna & Truntyagin, 2016;Sazanov, 2010 Polytechnic University has created a website that can be a powerful tool for building ICT competencies for teachers and students (Okushova, Stakhovskaya & Sharaev, 2016). However, the survey has found that only 6% of respondents regularly visit the site.…”
Section: Research Questionsmentioning
confidence: 99%